Cytochrome P450 1A2 Is Incapable of Oxidizing Bilirubin Under Physiological Conditions - Li, Xinyi; Yu, Dongzhen; Jie, Huiqun; Zhou, Huiqun; Ye, Haibo; Ma, Guo; Wan, Lili; Li, Chunyan; Shi, Haibo; Yin, Shankai (Frontiers in Pharmacology, 2019)
Background Bilirubin (BR) is metabolized mainly by uridine diphosphate (UDP)-glucuronosyltransferase 1A1 (UGT1A1) through glucuronidation in the liver. Some studies have shown that several subtypes of cytochrome P450 (CYP) enzymes, including CYP1A2, are upregulated by inducers and proposed to be alternative BR degradation enzymes. However, no information is available on the BR degradation ability of CYP in normal rats without manipulation by CYP inducers. Methods: Quantitative real-time polymerase chain reaction (QRT-PCR), western blot, immunofluorescence and confocal microscopy were used to find expression of CYP1A2 in the brain and the liver. BR metabolites in microsomal fractions during development were examined by high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (LC-MS/MS). Results: In the present study, we observed that CYP1A2 mRNA levels increased at postnatal days (P)14 and P30 with respect to the level at P7 both in liver and brain, this increment was especially pronounced in the brain at P14. The expression of CYP1A2 in the brainstem (BS) was higher than that in the cerebellum (CLL) and cortex (COR). Meanwhile, the CYP1A2 protein level was significantly higher in the cortex than in the brainstem and cerebellum at P14. The levels of BR and its metabolites (m/z values 301, 315, 333 and biliverdin) were statistically unaltered by incubation with liver and brain microsomal fractions. Conclusion: Our results indicated that the region-specific expression of CYP1A2 increased during development, but CYP family enzymes were physiologically incapable of metabolizing BR. The ability of CYPs to oxidize BR may be triggered by CYP inducers.